امام جوینی سے منسوب اختصاصی افکار شریعت کا جائزہ : مصالح و مقاصد شریعت کا تجزیاتی مطالعہ: An Examination of the Exclusive Thoughts Attributed to Imam Juwayni: An Analytical Study of the Objectives and Purposes of Sharia - Shoaib Siddique; Hafiz Samama Tahir; Zahoor Elahi (International Research Journal of Arabic and Islamic Studies, 2022)
Imam Juwayni, a seminal figure in Islamic jurisprudence during the 11th century, is renowned for his profound contributions to the understanding of Sharia, particularly in delineating its objectives and purposes (maqasid). This study undertakes a critical analysis of Imam Juwayni's distinctive viewpoints, aiming to elucidate their significance within Islamic legal theory. His insights into maqasid al-shariah, or the higher objectives of Islamic law, offer deep-seated ethical, social, and legal principles that guide the application of Sharia in diverse contexts.Juwayni's conceptual framework provides a robust foundation for exploring how Islamic law aims to preserve essential human interests, including safeguarding religion, life, intellect, progeny, and property. By scrutinizing Juwayni's interpretations and methodologies, this research examines their relevance across historical and contemporary contexts. It assesses the enduring impact of his ideas on Islamic jurisprudence, highlighting their implications for contemporary legal theory and practice.This analytical study engages with primary Islamic sources to contextualize Juwayni's perspectives, fostering a nuanced understanding of his intellectual legacy. By examining the dynamic interplay between legal theory and the broader objectives of Sharia, this research contributes to ongoing debates on the adaptation and application of Islamic law in the modern world.